Bach and Mozart essays on the enigma of genius - Marshall, Robert L. 1939- (Eastman studies in music, 2019)
Interpretive and biographical essays by a major authority on Bach and Mozart probe for clues to the driving forces and experiences that shaped the character and the extraordinary artistic achievements of these iconic composers